2023
DOI: 10.2147/opto.s390994
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the SRK/T Formula in Pediatric Cataract Surgery

Abstract: Purpose Determining IOL power is an important step in achieving the desired postoperative refractive target, but this determination remains challenging, as currently the used formulas were developed using IOL power calculations derived from adults. Patients and Methods This is a retrospective analytical study with the period of June 2018 to May 2019. All of the data were taken from medical records in referral tertiary eye hospital in Indonesia. All type of cataracts und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
1
2
Order By: Relevance
“…Others report lower predictability using the SRK/T formula as well, with a higher myopic shift, especially in young children, or short and normal eyes and lower amount of eyes within ±0.5 D from target refraction. [16][17][18][19][20][21][22] Others report a hyperopic shift for all of their tested formulas using second and third generation formulas, which is contrary to our results. 22 In previous studies, it was shown that in pediatric cataract surgery, the implantation of an IOL with posterior optic capture is the best alternative to prevent posterior capsule opacification.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Others report lower predictability using the SRK/T formula as well, with a higher myopic shift, especially in young children, or short and normal eyes and lower amount of eyes within ±0.5 D from target refraction. [16][17][18][19][20][21][22] Others report a hyperopic shift for all of their tested formulas using second and third generation formulas, which is contrary to our results. 22 In previous studies, it was shown that in pediatric cataract surgery, the implantation of an IOL with posterior optic capture is the best alternative to prevent posterior capsule opacification.…”
Section: Discussioncontrasting
confidence: 99%
“…Others report lower predictability using the SRK/T formula as well, with a higher myopic shift, especially in young children, or short and normal eyes and lower amount of eyes within ±0.5 D from target refraction. 16–22 Others report a hyperopic shift for all of their tested formulas using second and third generation formulas, which is contrary to our results. 22…”
Section: Discussioncontrasting
confidence: 99%
“…The SRK/T formulae did not show statistically significant differences in patients aged > 5 years. Irfani et al 22 studied the accuracy of SRK/T formula in pediatric cataract surgery; they reported MAE in age group < 7 years = 1.27 ± 1.18 D. The current study reported better outcomes with SRK/T with MAE = 0.73 + 0.55 D. The better results of the current study can be explained by A-constant optimization. Thanapaisal et al 23 also studied the accuracy of the SRK/T formula in pediatric cataract surgery and reported an MAE = 1.41 of 1.22 D. The reason for the higher MAE might be that they included traumatic and sulcus implantation cases.…”
Section: Discussionsupporting
confidence: 54%
“…Theoretical formulas are based on the adult schematic eye; they can be theoretically extrapolated better in children by proportionally downsizing the variables to pediatric dimensions. [20][21][22][23] In the current study, the SRK/T formula showed better results for the entire cohort. When subdividing the cases into two groups, SRK/T still showed superiority for patients aged between 2 and 5 years.…”
Section: Discussionmentioning
confidence: 89%